The review of promotional campaign “Visit Beautiful Terengganu 2017” on social media / Nurul Nadhirah Maamor and Nur Ellina Mohd Sahid - Maamor, Nurul Nadhirah; Mohd Sahid, Nur Ellina (2018)
First and foremost, the main purpose of this study is to review on the promotional campaign of ‘Visit Beautiful Terengganu 2017’. The researchers try to observe the comments at every photo and topic that the admin or other people share on the official social media. If the reviews that people respond are good, it means this kind of promotional campaign is effective and successful Other than that, the researchers are also intended to observe the outsiders’ awareness pertaining to this promotional campaign. This can be perceived by the researchers through the commentary section. If the comments are good, it means the government of Terengganu state already did their best along this campaign. Mostly, the followers for all of these official social media accounts are not from Terengganu. From the researchers’ review and perception, people are aware about this promotional campaign.